An approach to identify soil types by using hydraulic conductivity values - Maritha Nilam Kusuma; Wahyono Hadi; Budisantoso Wirjodirdjo; Yulfiah Yulfiah (Sustinere: Journal of Environment and Sustainability, 2018)
Water treatment in Indonesia still uses coagulant to reduce the contaminant. Therefore, an infiltration gallery is required as the pre-treatment before conventional water treatment conducted. Infiltration gallery is a natural technology for absorbing or filtrating the contaminant. The hydraulic conductivity plays the main role in soil filtration. There are many types of soil with different hydraulic conductivities. In infiltration gallery method it is important to identify the hydraulic conductivity value as the preliminary analysis because it is the important indicator to show the ability of soil to flow the water from one side to other sides when filtrating the contaminant. The slower the conductivity is, the better the quality of the water will be. The method used in this study was the Constant head Permeameter. The result of this study shows that the same type of soil type has different hydraulic conductivities.